Economies of scale in manufacturing industry - Pratten, C. F. (Cambridge [Eng.] : University Press, 1971)
One of the arguments used to support policies designed to reduce tariff barriers is that the expanded markets so provided will reduce unit production costs because of economies of scale
Includes bibliographical references.
sju 22/01/2019
Loans
Keywords: Costs, Industrial; Manufacturing industries; Economies of scale